2017
DOI: 10.1371/journal.pgen.1006982
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine stimulates pheromone-independent dimorphic transition in Cryptococcus neoformans by promoting Crz1 nuclear translocation

Abstract: Morphotype switch is a cellular response to external and internal cues. The Cryptococcus neoformans species complex can undergo morphological transitions between the yeast and the hypha form, and such morphological changes profoundly affect cryptococcal interaction with various hosts. Filamentation in Cryptococcus was historically considered a mating response towards pheromone. Recent studies indicate the existence of pheromone-independent signaling pathways but their identity or the effectors remain unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 96 publications
6
32
0
Order By: Relevance
“…To this end, we transformed the inducible promoter-driven and mCherry-tagged ZNF2 gene into the pas3 Δ mutant. As we have shown previously ( 40 ), Znf2 is localized to the nucleus ( Fig. 3E ).…”
Section: Resultssupporting
confidence: 89%
“…To this end, we transformed the inducible promoter-driven and mCherry-tagged ZNF2 gene into the pas3 Δ mutant. As we have shown previously ( 40 ), Znf2 is localized to the nucleus ( Fig. 3E ).…”
Section: Resultssupporting
confidence: 89%
“…These expression analyses suggest that pheromone response pathway activation per se is not sufficient to explain the ability to undergo unisexual reproduction and its association with competition for mating partners. It was previously shown that the cell fusion protein Prm1 is not required for unisexual reproduction [26], and certain environmental factors, such as copper and glucosamine, can induce hyphal growth independently of the pheromone response pathway [23, 24]. In a recent study on the quorum sensing peptide Qsp1, deletion of pheromone and pheromone receptor genes had little impact on hyphal growth during unisexual reproduction [25], further indicating the polygenic nature of unisexual reproduction.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, GlcNAc has been shown to inhibit hyphal growth in Candida tropicalis, although GlcNAc was still able to induce the White to Opaque switch [102,103], and it was not able to induce true hyphae in Candida dubliniensis [104]. It is also interesting that glucosamine, but not GlcNAc, can stimulate filamentous growth of Cryptococcus neoformans [105].…”
Section: Glcnac Can Stimulate or Inhibit Hyphal Morphogenesis In Othementioning
confidence: 99%